Poliostotic fibrous dysplasia in the left maxilla sinus. Case of presentation. - Félix Dueñas Ros; Nery María Díaz Yanes; Dianarelys Villafuerte Delgado (Medisur)
We present a clinic case of poliostotic fibrous dysplasia in the left maxilla sinus extended to Pterigopaltinar cavity and sphenoid sinus in a 26 year old woman who suffer from facial deformation. Paranasal x ray images didn’t permit to make the differential diagnosis between tumor or inflammatory lesions at the beginning, CT scan showed hiperdensy lesions like a tumor that suggest fibrous dysplasia. The final diagnosis was obtained by biopsy of the lesions.